Studies in symbolic interaction. - Denzin, Norman K. (Studies in symbolic interaction., 2012)
Part I, "Theoretical Openings," of Volume 39 of Studies in Symbolic Interaction contains outstanding contributions by leading interactionists on welfare reform, history, biography and memory. The three chapters in Part II, "Studies in Social Construction," interrogate the complexities of social interaction, interpersonal and professional identity, and the cinematic representation of alcoholism. Part III takes up important interpretive interventions on the topics of imagination and intimate deception in everyday life.